Prevalence of dental anomalies and bone alterations in children's panoramic radiographies - Jéssica Costa REIS; May Anny Alves FRAGA; Sérgio Lins DE-A; Maria Helena Monteiro de Barros MIOTTO; Teresa Cristina Rangel PEREIRA; Danielle Resende CAMISASCA (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Objective To verify the prevalence of dental anomalies in terms of number, position and shape, and the presence of bone alterations, through analysis of panoramic radiographs. Methods This study evaluated dental anomalies and bone alterations in children aged 6 to 12 years-old, detected on panoramic radiographies recorded in the radiographic database of the Federal University of Espírito Santo between 2012 and 2016. Clinical and demographic information were registered. Dental records were retrieved to obtain the medical history involving syndromes or other diseases that may interfere with the anomalies and alterations. Chi-square and exact Fischer's statistical tests were performed. Results There were alterations in 83 out of 301 panoramic radiographs analyzed. There were 169 anomalies or alterations (mean of 2,04±1,38 anomalies/patient), involving 201 teeth. The most prevalent anomaly was tooth impaction (26.63%), which affected the canines more frequently, followed by hypodontia (24.26%), more often found in the second premolar, and both affected mostly females. Hyperdontia and radiolucent lesions showed the same prevalence (18.93%), the most affected teeth were those of the anterosuperior region and the first mandibular molars, respectively. The least prevalent anomalies were dilaceration (7.69%), taurodontism (2.37%) and radiopaque lesions (1.18%). Bone alterations were significantly more found in mandible and in the posterior region, which confirms the prevalence in the lower molars. Conclusion Although there was no statistically significant difference regarding sex, there was a high prevalence of anomalies and alterations in our study population, which indicates the importance of its diagnosis by means of a panoramic x-ray examination.